The influence of impulse purchase orientation, brand orientation, prior online purchase experience and online trust on online purchase intention among working adults in Kuala Lumpur, Malaysia - Ilias, Hatta; A Rahman, Mohd. Khirzanbadzli; Wan Rashid, Wan Edura; Othman, Abdul Kadir; Saihaini, Shamsul Baharin; Sharkawi, Ismawati; Malini, Helma (Human Resource Management Academic Research Society, 2022)
The new trend of purchasing has changed tremendously from traditional method to online. The paper highlights the issue of the important factors encouraging online shopping among office workers. Thus the objective of the study is to determine the factors that influence online purchase intention. The factors involved in the study are impulse purchase orientation, brand orientation, prior online purchase experience, and online trust. Applying quantitative method, questionnaires using Google form were distributed through social media social network such as WhatsApp, Facebook, FB Messenger, and Microsoft Teams for data collection. Respondents were selected using snowball sampling technique for data gathering. The data were analysed using descriptive analysis, reliability, Pearson Correlation Coefficient and Multiple Regression Analysis by deploying the Statistical Package for the Social Sciences (SPSS). The major findings of the study revealed that impulse purchase orientation, brand orientation, prior online purchase experience and online trust have a significant relationship with online purchase intention. However, the results of Regression Analysis indicate that online trust has a strong influence on online purchase intention. As a concluding remark, the study suggested that the web retailers should consider providing more reliable and important information inside their web sites in order to increase customers’ trust. The practical and research implications are further discussed in the paper. Future researchers are recommended to conduct the study with wider scope of respondents.